Advanced Corneal Cross-Linking System with Fluorescence Dosimetry. (27th June 2012) - Friedman, Marc D.; Pertaub, Radha; Usher, David; Sherr, Evan; Kamaev, Pavel; Muller, David
Abstract : Purpose . This paper describes an advanced system that combines corneal cross-linking with riboflavin with fluorescence dosimetry, the ability to measure riboflavin diffusion within the cornea both before and during UVA treatment. Methods and Results . A corneal cross-linking system utilizing a digital micromirror device (DMD) was assembled and used to measure diffusion coefficients of 0.1% riboflavin in 20% dextran in porcine eyes. A value of ( 3.3 ± 0.2 ) × 10 − 7 cm 2 /s was obtained for the stroma. Diffusion coefficients for the transepithelial formulation of 0.1% riboflavin in 0.44% saline and 0.02% BAK were also measured to be 4.7 ± 0.3 × 10 − 8 cm 2 /s for epithelium only and ( 4.6 ± 0.4 ) × 10 − 7 cm 2 /s for stroma only. Riboflavin consumption during a UVA treatment was also demonstrated. Conclusion . A new advanced corneal cross-linking system with fluorescence dosimetry of riboflavin has been demonstrated. It is hoped that this method may play a significant role in determining the underlying mechanisms of corneal cross-linking and assist with the development of additional riboflavin formulations. Moreover, dosimetry may prove valuable in providing a method to account for the biological differences between individuals, potentially informing cornea-specific UVA treatment doses in real time.